Estradiol Supplement or Induced Hypertension May Attenuate the Angiotensin II Type 1 Receptor Antagonist-Promoted Renal Blood Flow Response to Graded Angiotensin II Administration in Ovariectomized Rats - Choopani, Samira; Nematbakhsh, Mehdi (Journal of the Renin-Angiotensin-Aldosterone System, 2022)
Backgrounds. Estrogen replacement therapy (ERT) and hypertension may influence females’ renin-angiotensin system (RAS) and its components. The angiotensin II (Ang II) type 1 receptor (AT1R) antagonist (losartan) may promote renal blood flow (RBF), and it is widely used in the clinic to control hypertension. The main objective of this study was the effects of estradiol or induced hypertension on RBF response to Ang II in losartan-treated ovariectomized (OVX) rats. Methods. Two groups of OVX rats were treated with placebo (group 1) and estradiol (group 2) for period of four weeks, and another group of OVX rats was subjected to induce hypertension by two-kidney one clip (2K1C) model (group 3). All the groups were subjected to the surgical procedure under anesthesia, and AT1R was blocked by losartan. RBF and renal vascular resistance (RVR) responses to Ang II administration were determined and compared. Results. Mean arterial (MAP) and renal perfusion (RPP) pressures in group 3 and uterus weight (UT) in group 2 were significantly more than other groups (P<0.05). Ang II infusion resulted in dose-related percentage change increase in RBF and decrease in RVR. However, these responses in the OVX-estradiol and OVX-hypertensive rats were significantly lower than in the OVX-control group (P<0.05). For instance, at the dose of 1000 ng/kg/min of Ang II administration, the percentage change of RBF was 45.1±10.4%, 17.9±2.3%, and 16.7±4.7% in the groups of 1 to 3, respectively. Conclusion. Losartan prescription in some conditions such as hypertension or ERT could worsen RBF and RVR responses to Ang II.